Humor in the Webtoon Nerd and Jock: A Pragmatic Study of Grice’s Cooperative Principle and Searle’s Illocutionary Acts (PANOPTICON: Journal of English Studies, 2026)
This study investigates how violations of Grice’s Cooperative Principle and Searle’s illocutionary acts contribute to humor construction in digital comics. While previous pragmatic studies have extensively examined humor in spoken discourse, films, and stand-up comedy, limited attention has been given to webtoons as a form of multimodal digital narrative. As a rapidly growing form of online entertainment that combines visual and verbal elements, webtoons provide a significant site for analyzing how humor operates within contemporary digital communication. The object of this study is the webtoon Nerd and Jock by Marko Raassina (2017). Employing a qualitative descriptive method, the data were collected through close reading and systematic documentation of selected episodes. The analysis applies Grice’s (1975) Cooperative Principle, which includes the maxims of quantity, quality, relevance, and manner, as well as Searle’s (1980) classification of illocutionary acts—assertive, directive, expressive, commissive, and declarative. The findings reveal 15 instances of maxim violations, with the maxim of relevance being the most frequently violated. Additionally, 38 illocutionary acts were identified, with expressive acts emerging as the most dominant type. The prominence of relevance violations and expressive illocutionary acts indicates that humor in Nerd and Jock is primarily constructed through unexpected conversational shifts and intensified emotional expressions. These findings highlight the role of pragmatic deviation in shaping humor within multimodal digital discourse.